Efficiency of Consolidation Dam (CD) Building on Sedimentation Rate of Irrigation Area (DI) Gumbasa River Sigi Central Sulawesi - Yulianti, Erni; Prasetyo, Eko (Migration Letters, 2024)
Sedimentation is one of the biggest challenges facing irrigation systems. Sedimentation can cause canal clogging, water quality decline, and irrigation efficiency loss. Consolidation Dams (CDs) are simple structures that can be used to reduce sedimentation. CDs slow the water flow, allowing sediment to settle behind the structure. This research was conducted to assess the effectiveness of CDs in reducing sedimentation in DI Gumbasa, Central Sulawesi. The study used quantitative and qualitative approaches to understand CDs’ impact comprehensively of CDs. The study results showed that CDs effectively reduce sedimentation in DI Gumbasa. The sedimentation rate decreased significantly in areas with CDs. This sedimentation reduction positively impacts irrigation efficiency, water quality, and community well-being. The study also found that CDs have a varying impact on different parts of the irrigation system. Stakeholder feedback is important to identify and address this variation. Overall, the study shows that CDs are an effective intervention for reducing sedimentation in irrigation systems. CDs can improve irrigation efficiency, water quality, and community well-being.